Enhanced electrocatalytic nitrate reduction to ammonia using plasma‐induced oxygen vacancies in CoTiO3 − x nanofiber. Issue 1 (14th July 2022) - Fan, Xiaoya; Liang, Jie; Zhang, Longcheng; Zhao, Donglin; Yue, Luchao; Luo, Yongsong; Liu, Qian; Xie, Lisi; Li, Na; Tang, Bo; Kong, Qingquan; Sun, Xuping
Abstract: Electrochemical nitrate (NO3 − ) reduction is a green and economic route for ammonia (NH3 ) synthesis. However, this conversion suffers from low NH3 selectivity due to strong competition from other NO3 − reduction pathways. Here, we report that a plasma‐induced defective CoTiO3 − x nanofiber with oxygen vacancies acts as an efficient electrocatalyst for NO3 − reduction to NH3 . In 0.1 M NaOH solution containing 0.1 M NO3 −, it is capable of achieving a remarkable NH3 yield of 30.4 mg h –1 mgcat. –1 and a high Faradaic efficiency of 92.6%. The catalyst also shows strong electrochemical stability for a 20‐h electrolysis test. Additionally, a Zn‐NO3 − battery using CoTiO3 − x as the cathode catalyst offers a peak power density of 5.04 mW cm −2 and a large NH3 yield of 3.08 mg h −1 mgcat. −1 . The catalytic mechanism is further discussed by density functional theory calculations. Abstract : A plasma‐induced CoTiO3 − x nanofiber with oxygen vacancies is a highly active electrocatalyst for converting NO3 − to NH3 at ambient conditions, achieving a remarkable NH3 yield of 30.4 mg h –1 mgcat. –1 and a high Faradaic efficiency of 92.6%.